2008
DOI: 10.1536/ihj.49.471
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sleep-Disordered Breathing Level and Acute Onset Time of Congestive Heart Failure

Abstract: SUMMARYSleep-disordered breathing (SDB) is frequently observed in patients with congestive heart failure. Recent studies have shown that SDB negatively affects the onset of congestive heart failure; however, no studies have addressed the relationship between the level of SDB and the onset time of acute dyspnea. We hypothesized that SDB affects the acute onset time of dyspnea (AOT) and investigated the relationship between SDB and AOT.We examined 80 patients (mean age, 61.6 years) with congestive heart failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Hypoxemia plays a crucial role in sympathetic nerve system activation in SAS patients, which is related to nocturnal HTN including secondary HTN and non-dipper blood pressure (BP) pattern, and triggers cardiovascular events [4]. Our previous studies reported the influence of sleep disordered breathing (SDB) on the acute onset time of dyspnea and chest pain in patients with congestive heart failure [5] and acute coronary syndrome [6]. Currently, 24h ambulatory blood pressure monitoring (ABPM) provides accurate BP assessment during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxemia plays a crucial role in sympathetic nerve system activation in SAS patients, which is related to nocturnal HTN including secondary HTN and non-dipper blood pressure (BP) pattern, and triggers cardiovascular events [4]. Our previous studies reported the influence of sleep disordered breathing (SDB) on the acute onset time of dyspnea and chest pain in patients with congestive heart failure [5] and acute coronary syndrome [6]. Currently, 24h ambulatory blood pressure monitoring (ABPM) provides accurate BP assessment during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Many investigators have reported that the risk of sudden death, heart failure or acute myocardial infarction increases during sleep in obstructive SAS patients. 5,6,19 These findings suggest that sleep BP control in these patients be desirable.…”
Section: Influential Factors In Circadian Bp Changesmentioning
confidence: 82%
“…Moreover, the incidence of nocturnal cardiovascular events while sleeping increases in these patients. [4][5][6] Chronic kidney disease (CKD) seems to be tightly linked with nocturnal hypertension and morning BP surge. 7 CKD poses a high risk for the onset of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…For convenience, subjects with AHI > 20 are designated in the text as having “high levels of OSA activity” and those with AHI < 20 as having “low levels OSA activity.” In a recent study by Gooneratne et al (24), an AHI above 20 was associated with a higher mortality hazard ratio. Further, this cut‐off level has been applied in studies examining how sleep disordered breathing relates to congestive heart failure (25) and outcomes after cardiac resynchronization therapy (25, 26).…”
Section: Methodsmentioning
confidence: 99%